2022
DOI: 10.1097/scs.0000000000008815
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Socioeconomic Disparities in Prompt Craniosynostosis Workup and Treatment

Abstract: The purpose of this study was to identify racial and socioeconomic disparities in craniosynostosis evaluation and treatment, from referral to surgery. Patients diagnosed with craniosynostosis between 2012 and 2020 at a single center were identified. Chart review was used to collect demographic variables, age at referral to craniofacial care, age at diagnosis, age at surgery, and surgical technique (open versus limited incision). Multivariable linear and logistic regression models with lasso regularization asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…These findings contribute to the current literature, which has described race, ethnicity, and insurance payor as socioeconomic predictors of delayed presentation and treatment in the craniosynostosis population. [14][15][16][17][18][19][20] Our study provided additional insight to factors such as parental education and household income, which have previously been defined as indicators of socioeconomic status. 26 Perhaps unsurprisingly, lower parental percent educational attainment and lower median household income were associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These findings contribute to the current literature, which has described race, ethnicity, and insurance payor as socioeconomic predictors of delayed presentation and treatment in the craniosynostosis population. [14][15][16][17][18][19][20] Our study provided additional insight to factors such as parental education and household income, which have previously been defined as indicators of socioeconomic status. 26 Perhaps unsurprisingly, lower parental percent educational attainment and lower median household income were associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Insurance payor, race, and median zip code income quartiles have been well-described socioeconomic indicators related to craniosynostosis management. [14][15][16][17][18][19][20] However, systematic review of the literature highlighted a knowledge gap surrounding geospatial disparities and other socioeconomic indicators such as parental education attainment. In addition, zip code-based metrics lack granularity and vary tremendously in size, shape, and population.…”
mentioning
confidence: 99%
“…Access to craniosynostosis evaluation and surgical care varied based on patient race, insurance status, and socioeconomic status (Table 1). Seventeen of the 28 studies analyzed differences in time to craniosynostosis diagnosis, referral, or surgical intervention (7 single-institution cohort reviews, 10 national database reviews, and 2 dual-institution cohort revi ews) 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Ten 3,4,[7][8][9]11,13,15,17,19 of the 17 studies investigated racial disparities in access to care, all of which found that non-white patients were more likely to experience a delay to at least one step of the diagnostic process (i.e., diagnosis, referral, or intervention) compared to White patients.…”
Section: Time To Diagnosis Referral and Interventionmentioning
confidence: 99%
“…Seventeen of the 28 studies analyzed differences in time to craniosynostosis diagnosis, referral, or surgical intervention (7 single-institution cohort reviews, 10 national database reviews, and 2 dual-institution cohort revi ews) 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . Ten 3,4,[7][8][9]11,13,15,17,19 of the 17 studies investigated racial disparities in access to care, all of which found that non-white patients were more likely to experience a delay to at least one step of the diagnostic process (i.e., diagnosis, referral, or intervention) compared to White patients. Seven studies found that Black and Hispanic patients were older at the time of surgery, 3,4,7,13,15,17,19 and 3 studies found that patients of these demographics were less likely to undergo surgery before 1 year.…”
Section: Time To Diagnosis Referral and Interventionmentioning
confidence: 99%
See 1 more Smart Citation